Intellectual property rights : innovation, governance, and the institutional environment - Andersen, Birgitte (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
This book has been framed too commonly in trems of refining and strengthening legal rights.
Includes bibliographical references and index.
aug 22/05/13, ijb 28/03/2019
Loans
Keywords: Intellectual property